(untitled) (Cadernos de Sociomuseologia, 2009)
In the present text we intend to analyse 5 basic documents that translate the Museological Thinking in our century and that, chiefly, have led professionals of the area to apply this “science” in a less hermetic way and to understand its practice. The option to study and analyse the documents results from the fact that they influence present day museological practice and thinking. It is impossible to speak of museology nowadays without referring to one of these documents, not to mention a few nations that have even modified and/or created specific laws for the management of their preservationist cultural policy. Anyway, we are aware that this text intends only to carry out a preliminary approach to the documents, in the sense that the wealth of its content would allow us to slowx over an infinity of issues that they raise. I specifically refer to the documents produced at UNESCO Regional Seminar on the Role of Museums in Education, which took place in Rio de Janeiro in 1958; at the Santiago Round Table in 1972, in Chile; at the 1rst New Museology International Workshop, in Quebec, Canada, 1984; at the Oaxtepec Meeting, in Mexico 1984; and at the Caracas Meeting in 1992. These are documents elaborated within the ICOM –International Council of Museums. These documents are the result of a joint reflection by professionals who seek the evolution of ideas within their areas of action, recognising that in order to do so it is necessary to leave the cocoon of the museological institutions and try to discuss their conceptual advances with professionals of related areas. It is important to be capacitated to reuse these advances in their areas of action. This is the recognition of the importance of interdisciplinarity for the museological context.